Organocatalytic Trans Semireduction of Primary and Secondary Propiolamides: Substrate Scope and Mechanistic Studies. Issue 1 (11th October 2021) - Grams, R. Justin; Lawal, Monsurat M.; Szwetkowski, Connor; Foster, Daniel; Rosenblum, Carol Ann; Slebodnick, Carla; Welborn, Valerie Vaissier; Santos, Webster L.
Abstract: We report a chemoselective, phosphine‐catalyzed semireduction of primary and secondary propiolamides. In the presence of stoichiometric pinacolborane and catalytic n ‐tributylphosphine, a variety of propiolamides were successfully converted to the corresponding acrylamides in excellent yield with ( E )‐stereoselectivity. The reaction condition is tolerant of various functional groups including alkene, alkyne, ketone, or ester. Deuterium labeling studies established that the hydride from activated pinacolborane is added to the α‐carbon and the proton on the amide nitrogen is abstracted by the ß‐carbon to furnish the ( E )‐acrylamides. DFT calculations revealed a clear energetic driving force for the ( E )‐ over the ( Z )‐isomer. Abstract :